Vitamin D Deficiency and its Impact on Depression among Al-Maarefa University Students, Riyadh, Saudi Arabia - Asdaq, Dr. Syed Mohammed Basheeruddin (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: Health science university students are exposed to a lot of issues that may lead to depression. A poor or unhealthy diet and lack of outdoor places for exercising due to hot weather are major reasons attributed for Vitamin D deficiency in Riyadh. The current study was designed to estimate the prevalence of Vitamin D deficiency and depression and explore if there is a relationship between them among university students. Materials and Methods: A cross-sectional comparative study survey was distributed to male and female students who study at Al-Maarefa Colleges of Science and Technology during March–May 2017 in Riyadh. The level of depression was measured by DASS 21 scale. Analysis of data was done using SPSS-IBM and P < 0.05 was considered significant. Results and Discussion: As participants of the current study were university students, most of them were in an age group of 20–22 years. Furthermore, the majority of the students volunteered to give their feedback in this questionnaire study were females (74%) when compared to male (26%). High percentage of surveyors in the female section was found with Vitamin D deficiency when compared to their male counterparts. Three scales of DASS 21 revealed a significant association between Vitamin D deficiency and depression. A significant relationship between low Vitamin D level and prevalence of depression is demonstrated in this study. Conclusion: Therefore, efforts are necessary to bring about awareness among university students to take effective steps to combat Vitamin D deficiency, and hence possible induction of depression could be avoided that might increase their academic performance.